Ocular changes in premature infants - Negareh Yazdani (Reviews in Clinical Medicine, 2017)
Introduction: This article aimed to review the literatures on visual impairments and ocular changes in premature infants with low birth weight and gestational age.Methods: Five electronic databases including: PubMed, Web of Science, Science direct, Ovid, and Scopus were searched. Original articles published until 2015 describing preterm infants were reviewed. Repetitive and derivative articles were excluded.Results: Out of 100 unique, potentially relevant articles, 42 studies that addressed and met the inclusion criteria were evaluated.Conclusion: Prematurity affects ocular structures (from anterior to posterior segment) and functions. Premature infants are at risk of myopization. Concerning the changes in premature infants, a significant increase is found in axial length, intraocular pressure, and central corneal thickness; moreover, high incidence of retinal changes is reported as a result of prematurity. On the other hand, visual acuity, tear, electroretinogram, and visual evoked potential responses decrease with prematurity. The most common ophthalmic disorders in preterm infants are myopia and retinopathy of prematurity, which could affect life quality due to reduced visual acuity.